Provenance of Oligocene lithic and quartz arenites of the East Carpathians: Understanding sediment routing systems on compressional basin margins. (17th September 2022) - Roban, Relu D.; Ducea, Mihai N.; Mihalcea, Vlad I.; Munteanu, Ioan; Barbu, Victor; Melinte‐Dobrinescu, Mihaela C.; Olariu, Cornel; Vlăsceanu, Mihai
Abstract: We present new sedimentological, petrographical, palaeontological and detrital zircon U–Pb data on late Oligocene–early Miocene sedimentary rocks of the thin‐skinned thrust belt of East Carpathians. These data were acquired to reconstruct the sedimentary routing system for two compositionally different turbidite fans made of the regionally extensive Kliwa and Fusaru formations. On the eastern margin of the Moldavides foreland basin, large low‐gradient river systems draining the East European Platform provided well‐sorted quartz‐rich sand forming deltas on wide shallow shelves and thick Kliwa submarine fans. Due to the westward subduction of a thinned continental plate, the western basin margin was characterized by short, steep‐gradient routing systems where sediment transport to deep water was mainly through hyperpycnal flows. The Getic and Bucovinian nappes of the East Carpathians and the exhumed Cretaceous–Early Palaeogene orogenic wedge fed Fusaru fans with poorly sorted lithic sand. The Fusaru fans trend northwards in the foredeep basin having an elongate depocentre, interfingering and then overlapping on the distal part of the Kliwa depositional system due to the eastward advance of the Carpathian fold‐and‐thrust belt. A smaller sediment input is supplied by southern continental areas (i.e. Moesian Platform, North Dobrogea and potentially the Balkans). In general, the sandstone interfingering between distinct basin floor fan systems is less well documented because the facies would be similar and there are not many systems that have a distinct sediment provenance like Kliwa and Fusaru systems. This case study improves the understanding of regional palaeogeography and sedimentary routing systems and provides observations relevant here or elsewhere on the interfingering turbidite fan systems. Abstract : Palaeogeographical reconstruction of the Moldavides Basin during Oligocene, depicting the drainage routes associated with the marine depositional systems (a); the cross‐section illustrating the advancing of the Carpathian indenter and the interfingering of the two turbidite systems supplied from opposite margins of the foreland basin (b).